Aplikasi mudah alih sistem maklumat geografi bagi penjagaan kesihatan orang kurang upaya (Mobile GIS applications for people with disabilities healthcare services) / Abdul Rauf Abdul Rasam …[et al.] - Abdul Rasam, Abdul Rauf; Azlin, Azri Haziq; Aiman Abu, Noraqila; Idris, Ahmad Norhisyam; Romeyu, Nurmilah (Universiti Teknologi MARA, 2020)
Disability is termed as both evolving concept and manifestation of interaction between persons with disabilities (PWDs) and physical and environmental barriers that holds them back from contributing actively in a society. People who fall in this category will find themselves trapped in a such vulnerable condition as they may not be able to cope with their daily problems without high surveillance from their guardian. Development of a mobile apps and web GIS-based healthcare system in Ampang is proposed in this study as this application has a bright potential to assist PWDs in terms of accessibilities to reach healthcare centres. The main objectives of this paper are i) to study the needs assessment on the proposed system, ii) to develop a mobile and web GIS-based 88 healthcare information system and iii) to evaluate the performance of the proposed system. Selected respondents agreed on the development of the prototype system, namely the mobile apps and web system. The system was created with main menus such as doctor home visits, ambulance and medication delivery. Medical support team can also perform analyses in the system for PWD needs such as shortest path analysis, buffering and view of the main menus.